Pregunta
Solve for \( u \). \[ \begin{array}{l}0.2 u=-0.5+3(0.8 u+0.9) \\ u=\square\end{array} \]
Ask by Li Ellis. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( u = -1 \)
Solución
Solve the equation \( 0.2u=-0.5+3(0.8u+0.9) \).
Solve the equation by following steps:
- step0: Solve for \(u\):
\(0.2u=-0.5+3\left(0.8u+0.9\right)\)
- step1: Simplify:
\(0.2u=2.2+2.4u\)
- step2: Move the variable to the left side:
\(0.2u-2.4u=2.2\)
- step3: Subtract the terms:
\(-2.2u=2.2\)
- step4: Change the signs:
\(2.2u=-2.2\)
- step5: Divide both sides:
\(\frac{2.2u}{2.2}=\frac{-2.2}{2.2}\)
- step6: Divide the numbers:
\(u=-1\)
The solution to the equation \(0.2u=-0.5+3(0.8u+0.9)\) is \(u=-1\).
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Extra Insights
To solve for \( u \), we start with the equation: \[ 0.2 u = -0.5 + 3(0.8 u + 0.9) \] First, we simplify the right side of the equation: \[ 0.2 u = -0.5 + 3 \times 0.8 u + 3 \times 0.9 \] \[ 0.2 u = -0.5 + 2.4 u + 2.7 \] \[ 0.2 u = 2.2 + 2.4 u \] Now, we want to isolate \( u \). Next, we can combine like terms: \[ 0.2 u - 2.4 u = 2.2 \] \[ -2.2 u = 2.2 \] To solve for \( u \), we divide both sides by -2.2: \[ u = \frac{2.2}{-2.2} = -1 \] Thus, the solution is: \[ u = -1 \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium